ANALISIS PENGARUH SUHU DAN KELEMBAPAN TERHADAP PERKEMBANGAN PENYAKIT Tobacco mosaic virus PADA TANAMAN CABAI - Taufik, Muhammad; Sarawa, Sarawa; Hasan, Asmar; Amelia, Kiki (Jurnal Agroteknos, 2013)
Climate, particularly environmental temperature, plays an important role in diseases caused by plant viruses. This study investigated the role of environmental temperature and humidity on development of Tobacco mosaic virus (TMV) on pepper (Capsicum anuum L). The research was conducted by using regression analysis. The results showed that TMV infection in plants could inhibit the growth of chili peppers. The temperature influenced disease development of TMV for up to 56,6%, whereas the humidity did not influence TMV disease development. Keywords: temperature, humadity, TMV, disease development, pepper